Financial Markets Integration: Appraising the Developed and Emerging Markets Nexus - Onakoya, Adegbemi Babatunde; Seyingbo, Victor Adedotun (International Journal of Economics and Financial Issues, 2017)
While many economists see financial globalization (financial markets integration) as critical to the development and strengthening of middle-income emerging markets, many have opined that financial integration carries huge risk that far outweighs potential benefits for most middle-income countries. This study therefore investigated the interdependence between emerging markets and developed markets. The study deployed the Diebold and Yilmaz methodological approach to investigate spill-over between markets. The research concluded that there exists interdependence between developed markets and emerging markets. The net benefits argument of financial markets held. Given increasing globalization none of the markets, whether developed or emerging is immune from the dynamics of global markets with consequential beneficial and deleterious impacts. The study recommended that emerging markets should institute reforms capable of enhancing a beneficial involvement in the global integration of financial markets. Macroeconomic reform is crucial if economies will benefit from financial markets integration. Exchange rate, inflation, fiscal deficits policies must be such that communicates macroeconomic stability, as this in turn suggests an investible territory to investors. Keywords: Financial Markets Integration, Stock market spill overs, Spill over index, VAR, Volatility transmission JEL Classifications: C13, C23, C81 E44, N20